Histopatologis Dugaan Edwardsiella tarda sebagai Penyebab Kematian Ikan Maskoki (Crassius auratus) : Postulat Koch - Atik Ratnawati; Uni Purwaningsih; Kurniasih . (Jurnal Sain Veteriner, 2013)
ABSTRACT              The aim of the study was to know the influence experimental infection of Edwardsiella tarda  was isolated from sick koi fish (Cryprinus caprio) to the histologic features of liver, kidney, gill, brain, intestine and muscle in Goldfish (Carassius auratus) based on Koch Postulate. Three goldfishes (KK) were used in this reseach. KK was infected by Edwardsiella tarda as much as 0.1ml i.m.. KK1 died on the 4th day and KK2 and KK3 died on the 25th day. All the fishes were then necropsied. The livers, kidneys, gills, brains, intestines and muscles were taken for making the histopathologic preparation. Bacteriologic observation of KK1 was conducted by cultivating the bacteria into Brillliant Green Agar (BGA), Triple Sugar Iron Agar (TSI Agar), Urea Agar, Motility Agar, Peptone Broth, sugars and oksidation test.      Result of histopathologic observation showed that there was necrosis, congestion and macrofag limpocytes and neutrophisl infiltrations in the livers,colloid mass and melanomacrofages in the kidney, congestion and proliferation of secondary lamellae, limfosit and macrofag infiltration of the brain, a melanomacrofag of the muscle and the intestine showed there was limphocytes, and macrofages infiltration in the brain, and melanomacrofages in the muscles as well. It was suspected that those bacteria was  Edwardsiella tarda.